Correlation Between History of Birth Control Usage and Incidence of Gingivitis among Pregnant Women in Ambulu Public Health Center, Jember District: A Cross-sectional Study - Rosanti, Nadia Dian; Perwitasari, Dinar Rizqi; Fa’ni, Renidya Asyura Muttabi’ Deya (Al-Hijrah Indonesia, 2023)
Using birth control (BC) can affect gingiva tissue, increasing the risk of developing gingivitis among women of reproductive age. Based on the Central Bureau of Statistics census, in 2021 61,77% of women in their reproductive age have used contraception and birth control in East Java. This study aims to find the correlation between the history and birth control usage and the incidence of gingivitis among pregnant women in Ambulu Public Health Center. This study uses a cross-sectional method with an analytical observational approach on pregnant women who visited the Dental Outpatient and received dental examinations in April and May of 2022. Thirty respondents were gathered with a history of birth control usage and evaluated using the dentist's Periodontal Index (PI). The results show that nine respondents (30%) had no history of using BC, two respondents (6.6%) used BC pills, ten respondents (33.3%) used 1-month injection BC, five respondents (16.6%) used 3-month injection BC, two respondents (6.6%) used implants BC and two respondents (6.6%) used IUD. From the cross table, one respondent (3.3%) was in the normal category, 1 respondent (3.3%) was in the simple gingivitis category, 15 respondents (50%) were in the early destructive periodontal disease category, and 13 respondents (43.4%) were in the destructive periodontitis. The data are analyzed using Chi-square result, showing that the significant value is p = 0,049 (p<0,05), so it can be concluded there is a significant relation between history of birth control usage and incidence of gingivitis in Ambulu Public Health Center. Dental and oral examinations are highly recommended in routine as early detection of health problems among pregnant women.